Análisis de la administración de heces fermentadas de porcinos en el control de enfermedades intestinales del cerdo - Ledesma Bonilla, Cristina Lisbeth (2020)
SUMMARY Intestinal health encompasses a number of physiological and functional characteristics including the digestion and absorption of nutrients, a stable and appropriate microbiota, as a purpose to show an alternative for pork farms based on the reuse of pork excreta as permissible results of anaerobic fermentation that aim to use prebiotic with satisfactory results to improve productive and health behavior in animals. Bibliographic research treatment on the analysis of the administration of fermented faeces of pigs, identifying the form of control in intestinal diseases of pork. The Inductive-Deductive method, bibliographic documentary, information obtained from the dspace of universities and scientific journals was used. The results showed that the inclusion of 70% excreta, 30% molasses and 3% bacterial growth stimulators (IBs) in a fermentation time of 30 days results in a material of optimal conditions, a high concentration of lactic acid is generated, with a concentration of 69 g/litre, generating acid-lactic bacteria, generated lactobacillus plantarum, pediococcus acidilactici at concentrations of 4x10.7 UFC/g. The research concludes that the physicochemical characteristics that occur during the fermentation stage such as: pH, odor, color. PH; in this medium of anaerobic fermentation increases the presence of lactic acid bacteria, producing an acidity that inhibits the proliferation of bacteria.